Early essential newborn care is associated with increased breastfeeding: a quasi-experimental study from Sichuan Province of Western China - Wang, Chen-ran; Li, Xia-yun; Zhang, Lin; Wu, Lin-man; Tan, Ling; Yuan, Fei; Guo, Yao; Williams, Sarah; Xu, Tao (International breastfeeding journal, 2020)
Breastfeeding is critical to promote maternal and child health. China has set national targets to further improve the exclusive breastfeeding rate. We aimed to examine associations between the provision of early essential newborn care (EENC) and breastfeeding outcomes among full term vaginally delivered neonates in the first 6 months of life. We conducted a quasi-experimental study in eight maternal and children's hospitals in Mianyang City and Deyang City in Sichuan Province of western China. Four hospitals were randomly selected as the intervention group with the implementation of EENC while others as the control group receiving routine care. We assessed effects of EENC on breastfeeding initiation time, duration of first-time breastfeeding, and exclusive breastfeeding rates up to 6 months of age. Data were collected after delivery, at hospital discharge, 1 month, 3 months, and 6 months post birth in the baseline phase from May to June 2017 and post-EENC phase from October to December 2017. We performed univariate analyses to ascertain differences between the two groups, and difference in difference (DID) models to explore the net effects. Of the 1349 enrolled mother and newborn pairs in our study, 1131 (83.9%) were followed up at 1 month of age, 1075 (79.7%) at 3 months, and 981 (72.7%) at 6 months. EENC was associated with earlier median time to initiate breastfeeding (25 min vs. 33 min, P <  0.01), an increased chance of successful first-time breastfeeding (OR 5.53; 95% CI 2.69, 11.40), longer duration of skin to skin contact (SSC) (21.53 min; 95% CI 18.17, 24.89) and longer duration of the first breastfeed (4.16 min; 95% CI 2.10, 6.22), and an increased likelihood of being exclusively breastfed at discharge (74.5% vs. 55.0%, P <  0.001), 3 months (OR 3.20; 95% CI 1.01, 10.15), and 6 months (OR 4.91; 95% CI 1.71, 14.13) of age. EENC enhances breastfeeding initiation and increases exclusive breastfeeding at 6 months of age. Our evidence suggests that nationwide scale up of EENC would increase the exclusive breastfeeding rate in the first 6 months of life.